"distinctly in a nineteenth century style": Samuel Hurst Seager's Christchurch Municipal Offices - Lochhead, Ian (Architectural History Aotearoa, 2021)
In 1887 Samuel Hurst Seager described his recently completed Christchurch Municipal Buildings, as being "distinctly in a nineteenth century style." The building was the result of an architectural competition and was the architect's first commission following his return to New Zealand after a period of study in Britain. From a twenty first-century perspective we recognise the Municipal Buildings as a precocious New Zealand example of the Queen Anne style that had come into vogue in Britain in the 1870s. Seager, however, clearly aimed to present his building not as belonging to a particular style from the past but as a representative design of the age in which it was built. Where we see an eclectic amalgam of sources drawn from British and European architecture from the late seventeenth-century onwards, Seager saw a synthesis of motifs that produced a picturesque effect appropriate to the building's site. For Seager, it seems, eclecticism was indeed the style of the nineteenth century. Drawing on contemporary sources, including the architect's description of the building that accompanied his competition entry, this paper examines Seager's design in the context of late nineteenth-century discussions of architectural style but also within the specific context of Seager's personal search for a resolution of the nineteenth-century "dilemma of style."